Proposed upgrading works of an administration office at Bangunan Fakulti Latihan Pegawai KD Pelandok for Kolej Tentera Laut Diraja, KD Sultan Idris I at Pangkalan TLDM 32100 Lumut, Perak / Nurliana Khalid - Khalid, Nurliana (2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student's knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Propose Upgrading Works of an Administration Office at Bangunan Fakulti Latihan Pegawai KD Pelandok for Kolej Tentera Diraja Malaysia, KD Sultan Idris I, Pangkalan TLDM 32100, Lumut, Perak. The Royal Malaysian Navy (RMN) (Malay: Tentera Laut DiRaja Malaysia (TLDM) is the naval arm of Malaysia's armed forces. KD SULTAN IDRIS I or called KDSI I is located in Lumut Royal Malaysian Navy ( RMN ) base ( Pangkalan TLDM ) and built specifically to train young officers and officer expertise. KDSI I was commissioned on May 15, 2006 by DYMM Paduka Seri Sultan Perak. As a Navy officer training center, it plays an important role for realizing and implementing policies and Navy maritime defense doctrine and especially the Malaysian Armed Forces in general. This central core objective is to educate and train young officers and also implement and coordinate courses expertise to Navy officials and foreign countries such as Myanmar, Sudan, Thailand, Vietnam, Oman and Fiji. The environment of the lobby need to be considered in terms of colour scheme as the main administration building and it does not have a strong sense of welcoming. The aim of this project is to upgrade the whole lobby and administration area by providing a better place to start off the day especially to the staff and trainees while giving a higher perspective view of thinking and impact to the environment suits the quality of an officer compatible with the modern era institutions. The objectives of this project include identifying the spatial design requirements and traffic flow from lobby through the office while creating a welcoming environment and organizing a proper furniture arrangements. The concept for this project is compartment which means a part or space marked or partitioned off. It at the same time will reflect the image of Navy who are disciplined and competent while implements a modern, flexible and evolving concept that corresponded to their image. KDSI I as a Navy officer training center, it plays an important role for realizing and implementing policies and Navy maritime defense doctrine and especially the Malaysian Armed Forces in general. The Administration Office of KDSI I is suitable to be upgraded because of upcoming and fast development of surroundings in the base in particular so that it will become outstanding and give the best impression to others. The modern office also requires versatility and dynamism - it must be flexible enough to quickly adapt to a range of uses. It must be aesthetically pleasing, and should encourage interpersonal communication amongst employees, while significantly lessening outdated hierarchical barriers. Work environments impact significantly on the wellbeing of employees and companies are increasingly recognizing the benefits of not only by financial concerns, but also social and environmental issues.